To switch or not to switch: results of a nationwide guideline of mandatory switching from originator to biosimilar etanercept. One-year treatment outcomes in 2061 patients with inflammatory arthritis from the DANBIO registry. Issue 2 (5th November 2018) - Glintborg, Bente; Loft, Anne Gitte; Omerovic, Emina; Hendricks, Oliver; Linauskas, Asta; Espesen, Jakob; Danebod, Kamilla; Jensen, Dorte Vendelbo; Nordin, Henrik; Dalgaard, Emil Barner; Chrysidis, Stavros; Kristensen, Salome; et al.
Abstract : Objectives: Real-world evidence on effectiveness of switching to biosimila r etanercept is scarce. In Denmark, a nationwide guideline of mandatory switch from 50 mg originator (ETA) to biosimilar (SB4) etanercept was issued for patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthritis (AxSpA) in 2016. Clinical characteristics and treatment outcomes were studied in ETA-treated patients, who switched to SB4 (switchers) or maintained ETA (non-switchers). Retention rates were compared with that of a historic cohort of ETA-treated patients. Switchers who resumed ETA treatment (back-switchers) were characterised. Methods: Observational cohort study based on the DANBIO registry. Treatment retention was explored by Kaplan-Meier plots and Cox regression (crude, adjusted). Results: 1621 (79%) of 2061 ETA-treated patients switched to SB4. Disease activity was unchanged 3 months' preswitch/postswitch. Non-switchers often received 25 mg ETA (ETA 25 mg pens/syringes and powder solution were still available). One-year adjusted retention rates were: non-switchers: 77% (95% CI: 72% to 82%)/switchers: 83% (79% to 87%)/historic cohort: 90% (88% to 92%). Patients not in remission had lower retention rates than patients in remission, both in switchers (crude HR 1.7 (1.3 to 2.2)) and non-switchers (2.4 (1.7 to 3.6)). During follow-up, 120 patients (7% of switchers) back-switched to ETA. Back-switchers' clinical characteristics were similar to switchers, and reasons for SB4 withdrawal were mainly subjective. Conclusion: Seventy-nine per cent of patients switched from ETA to SB4. After 1 year, adjusted treatment retention rates were lower in switchers versus the historic ETA cohort, but higher than in non-switchers. Withdrawal was more common in patients not in remission. The results suggest that switch outcomes in routine care are affected by patient-related factors and non-specific drug effects.